Metabolic Perturbations Caused by the Over-Expression of mcr-1 in Escherichia coli - Liu, Yi-Yun; Zhu, Yan; Wickremasinghe, Hasini; Bergen, Phillip J.; Lu, Jing; Zhu, Xiao-Qing; Zhou, Qiao-Li; Azad, Mohammad; Nang, Sue C.; Han, Mei-Ling; Lei, Tao; Li, Jian; et al. (Frontiers in Microbiology, 2020)
Rapid dissemination of the plasmid-born polymyxin resistance gene mcr-1 poses a critical medical challenge. MCR-1 expression is tightly controlled and imposes a fitness cost on the bacteria. We used growth studies and metabolomics to examine growth and metabolic changes within E. coli TOP10 at 8 and 24 h in response to different levels of expression of mcr-1. Induction of mcr-1 greatly increased expression at 8 h and markedly reduced bacterial growth; membrane disruption and cell lysis were evident at this time. At 24 h, the expression of mcr-1 dramatically declined with restored growth and membrane integrity, indicating regulation of mcr-1 expression in bacteria to maintain membrane homeostasis. Intermediates of peptide and lipid biosynthesis were the most commonly affected metabolites when mcr-1 was overexpressed in E. coli. Cell wall biosynthesis was dramatically affected with the accumulation of lipids including fatty acids, glycerophospholipids and lysophosphatidylethanolamines, especially at 8 h. In contrast, levels of intermediate metabolites of peptides, amino sugars, carbohydrates and nucleotide metabolism and secondary metabolites significantly decreased. Moreover, the over-expression of mcr-1 resulted in a prolonged reduction in intermediates associated with pentose phosphate pathway and pantothenate and CoA biosynthesis. These findings indicate that over-expression of mcr-1 results in global metabolic perturbations that mainly involve disruption to the bacterial membrane, pentose phosphate pathway as well as pantothenate and CoA biosynthesis.